Бемби: лесная сказка / Феликс Зальтен - Зальтен Феликс (Книги - мои друзья, 2013)
Экземпляры: ф.7 (20140127) / Инвентарный номер: 48248 / Цена: 67.50 / Авт.знак: З-25 / ГРНТИ: 17.82.93 / ББК: 84(4Авс)-4